CHARACTER BASED-AREA LEARNING MODEL IN YOUNG CHILDREN - Nurul Maulana Putri; Sulistiawati Sari; Sarah Setianingsih; RR. Deni Widjayatri (Journal of Early Childhood Education (JECE), 2021)
Early Childhood Education (ECE) is an effort to foster children from birth to the age of six, which is carried out by providing educational stimuli to help physical and spiritual growth and development so that children have further readiness. Character development is very important to start early. At the age of childhood or the golden age, it is proven to determine a child's ability to develop his potential greatly. Several early childhood learning models include classical, group, and area learning models based on activity angles and BCCT learning models. This study aims to develop the character of early childhood with the area learning model. This study uses a biographical approach, and the type of research used is a literature study. The results of this study provide opportunities for students to choose or carry out their activities according to their interests. Early childhood character development with the area learning model will be more interesting, interactive, and fun if teachers and students work together for the quality of learning that can be improved in a better direction.